Pembelajaran Al-Qur’an Masa Pandemi di Kecamatan Kota Kefamenanu Kabupaten Timor Tengah Utara - Sri Ujiana Putri (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
The Quran is a very perfect human guideline, because it regulates all aspects of human life, both worldly life including very small things and the afterlife. The Quran is an eternal book until the end of time as well as studying it. This paper aims to analyze the Quran learning during a pandemic in Kota Kefamenanu District, North Timor Tengah Regency. The Quran learning during the pandemic was divided into two, namely learning at the Al-Muhajirin Mosque TPA and learning the Quran for teenagers at home. This activity is carried out to practice knowledge and be willing to devote oneself for the benefit of humanity in general and the people of Kefamenanu City in particular. Even though independent KKN is carried out separately, it has very high enthusiasm. This Quran learning activity was carried out in the City of Kefamenanu at a mosque and private house, the face-to-face teaching and learning process ran smoothly until it was finished even in the midst of a pandemic. Parents also feel very happy because even during the pandemic their children can still study well and are not far from their respective homes so that they can be monitored.